Networking and Applying to Radiation Oncology During A Pandemic: Cross-Sectional Survey of Medical Student Concerns - Pollom, Erqi L. (Adv Radiat Oncol, 2021)
PURPOSE: We assessed the effectiveness of a virtual networking session tailored for third- and fourth-year medical students interested in radiation oncology, and report students’ concerns about applying to radiation oncology during the pandemic. METHODS AND MATERIALS: A multi-institutional networking session was hosted on Zoom and included medical students, faculty, and residents from across the country. The breakout room feature was used to divide participants into smaller groups. Participants were randomly shuffled into new groups every 10 to 15 minutes. Students completed pre- and post-session surveys. RESULTS: Among the 134 students who registered, 69 students participated in the session, and 53 students completed a post-session survey. Most students reported the session was valuable or very valuable (79%), and it was easy or very easy to network through the virtual format (66%). After the session, 18 (33.9%) students reported their interest in radiation oncology increased, and 34 (64.2%) reported their interest remained the same. Most students believed COVID-19 (55%) and virtual interviews and platforms (55%) negatively or somewhat negatively affected their ability to select a residency program. Most students (62%) were concerned they will be inaccurately evaluated as an interviewee on a virtual platform. Although 30% agreed or strongly agreed the cost-savings and convenience of virtual interviews outweigh potential downsides, 66% of students were planning to visit cities of interest in person before rank list submission. CONCLUSIONS: Medical students reported significant concerns with their ability to be accurately evaluated and to choose among residency programs on a virtual platform. Students found the networking session to be a valuable resource for most students, and programs could continue similar efforts during the residency application cycle to better represent their program while maintaining certain financial and geographic advantages of a virtual environment.